W pętli zadłużenia kredytowego. Przyczynek do społecznego portretu dłużników z perspektywy pokoleniowej = In the Loop of Credit Debts. Contribution to the Social Portrait of Debtors From the Generational Perspective - Mordzon, Adam (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article attempts to answer the question about the social dimension of the causes and consequences of credit consumption in Poland in recent years. The author aims at sketching possible framework to analyze this phenomenon. He asks whether one can speak in Poland about three faces of consumption for three generations of Poles.
Keywords: kredyt; zadłużenie; pętla zadłużenia; styl życia; presja konsumpcyjna